Strategi pemasaran ikan kering tawar dan dampaknya terhadap ekonomi keluarga di Desa Sungai Lueng Kecamatan Langsa Timur - Mastura; Vira Magvirah; Tajul ‘Ula (JIM: Jurnal Ilmiah Mahasiswa, 2025)
This study aims to determine the marketing strategy for dried freshwater fish, the impact of dried freshwater fish business on the family economy and what factors inhibit the marketing of dried freshwater fish in Sungai Lueng Village, Langsa Timur District. The research method used is a descriptive qualitative research method, with data collection through in-depth interviews and observations. The respondents in this study were Mrs. Nurlinawati, Mrs. Rosliana, Mrs. Nurmala, and 5 employees of Mrs. Nurlinawati's dried freshwater fish business. The results of the study showed that the dried freshwater fish business made a major contribution to increasing income for Mrs. Nurlinawati and for employees of this dried freshwater fish business, while the results of the study for Mrs. Rosliana and Mrs. Nurmala showed that the results of this dried freshwater fish business did not contribute to increasing their income. Although there are several inhibiting factors in marketing. The main obstacle is the lack of access to marketing on other social media platforms, which limits market reach so that marketing is not optimal, this is a challenge in promoting products.